Estimating RNA editing efficiency of five editing sites in the serotonin 2C receptor by pyrosequencing - IWAMOTO, KAZUYA (Copyright 2005 by RNA Society, 2005)
Accumulating evidence suggests that altered RNA editing of the serotonin 2C receptor (HTR2C) is involved in the pathophysiology of mental disorders and the action of antidepressants. Estimating RNA editing of HTR2C in various samples is a first step to understanding its pathophysiological roles. Here, we developed a high-throughput quantification method of RNA editing efficiency by pyrosequencing. By optimizing the dispensation order, the RNA editing efficiency of all five RNA editing sites including consecutively ordered sites in HTR2C was obtained. More importantly, our method made it possible to determine the content of partial HTR2C isoforms, which enabled us to monitor possible functional changes of HTR2C. This method was validated in both oligonucleotide and RT-PCR product templates, and showed good correlation with conventional cloning-sequencing analysis. Our method could be a valuable tool in the rapid assessment of RNA editing status, including assessment of natural variations, alterations in disease tissues, and responses to drugs.